2022
DOI: 10.1016/j.tranon.2021.101303
|View full text |Cite
|
Sign up to set email alerts
|

Sertraline repositioning: an overview of its potential use as a chemotherapeutic agent after four decades of tumor reversal studies

Abstract: Highlights Thirteen different neoplasms were shown to be susceptible to the antidepressant drug sertraline. The mechanisms of action through which sertraline can kill tumor cells are apoptosis, autophagy, and drug synergism. Sertraline inhibits TCTP, a tumor protein involved in cell survival pathways, responsible for reducing p53 levels. The testing of sertraline in vitro and in vivo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 64 publications
(201 reference statements)
0
5
0
1
Order By: Relevance
“…In addition to its use as an antidepressant, SRT has also been explored for other therapeutic applications. In vitro and in vivo studies have demonstrated its potential application in treating osteomyelitis infection [ 38 ] and cancer [ 39 ]. Furthermore, SRT presents antiparasitic [ 40 ], antibacterial [ 41 ], and antifungal activities against various pathogenic fungi, including C. neoformans [ 10 , 11 ], Aspergillus fumigatus [ 7 ], Trichosporon asahii [ 12 ], Sporothrix schenckii [ 9 ], and T. rubrum [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its use as an antidepressant, SRT has also been explored for other therapeutic applications. In vitro and in vivo studies have demonstrated its potential application in treating osteomyelitis infection [ 38 ] and cancer [ 39 ]. Furthermore, SRT presents antiparasitic [ 40 ], antibacterial [ 41 ], and antifungal activities against various pathogenic fungi, including C. neoformans [ 10 , 11 ], Aspergillus fumigatus [ 7 ], Trichosporon asahii [ 12 ], Sporothrix schenckii [ 9 ], and T. rubrum [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that TCTP was more expressed in high-grade gliomas and indicated worse prognosis, in the adulthood, whereas its expression decreased in tumor reversion phenomena, a biological process in which neoplastic cells lose its malignant phenotype ( Amson et al, 2013 ; Tuynder et al, 2004 ). Moreover, TCTP has been studied as a therapeutic target, and sertraline, an antidepressant, has been shown to inhibit TCTP levels, thus increasing p53 expression, and inducing tumor reversion ( Amson et al, 2013 ; Baú-Carneiro et al, 2022 ; Boia-Ferreira et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, downregulation of TCTP has been associated with increased tumour reversion phenotype 8 . TCTP has been reported to be a pharmacological target of clinical drugs Sertraline, Thioridazine and Dihydroartemisinin (DHA) 9,10 . Over the past two decades, TCTP has emerged as an important factor in cancer development, although its role in oral cancer progression has rarely been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…8 TCTP has been reported to be a pharmacological target of clinical drugs Sertraline, Thioridazine and Dihydroartemisinin (DHA). 9,10 Over the past two decades, TCTP has emerged as an important factor in cancer development, although its role in oral cancer progression has rarely been investigated. Thus, the present study attempts to investigate the clinical and functional significance of TCTP expression in oral cancers.…”
Section: Introductionmentioning
confidence: 99%